Implementasi Sistem Pemantauan Suhu dan Kelembapan Udara Berbasis Protokol AMQP - Edgar Juvianno Santoso; Rakhmadhany Primananda; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Indoor air quality is a problem that needs attention because it will affect human health. To maintain indoor air quality, there is a need for a system that can monitor temperature and humidity in the room. This monitoring system can be realized by using the Internet of Things (IoT) technology. In implementing IoT technology, a data communication protocol is needed to share data between each node in the IoT infrastructure. One of the frequently used data communication protocols is AMQP (Advanced Message Queuing Protocol). The use of the AMQP protocol in this study is supported by the condition of home networks that are considered to meet the needs of AMQP. With air temperature and humidity monitoring system, it is expected that the air quality in the room can be monitored properly. This study provides results that the implementation of the AMQP protocol on air temperature and humidity monitoring systems was successfully carried out and from the test results of the system reliability testing showed that the system was able to handle up to 210 Producers with Broker's devices memory usage of 0.4132 MB and Consumer's devices at 0.8345 MB.